Increasing returns to scale and the long-run Phillips curve - Andrea Vaona; Dennis J. Snower (Kiel Institute for the World Economy (IfW), 2006)
A growing body of empirical evidence shows that there exists a long-run positive tradeoff between inflation and real macroeconomic activity. Within a New Keynesian framewok, we examine how increasing returns generate a positive long-run relation between inflation and output.
Keywords: E3; E20; E40; E50; 330; Inflation; Increasing returns; Nominal inertia; Monetary policy; Phillips curve; Phillips-Kurve; Skalenertrag; Ungleichgewichtstheorie; Theorie